Critical Thinking: The MIT Essential Knowledge Series (Academic Journal of Internal Affairs, 2022)
Aim: The MIT Press Essential Knowledge series provides the reader with accessible, concise, yet interesting and completely up-to-date information. Till now, we have reviewed the following members of the series: Neuroplasticity, Anticorruption, Collaborative Society.Methodology: Each part was written by excellent experts on the subject, in a language understood by non-experts, too. In this way, the current research data and results in the field of each topic can be really used. Nowadays, it is not easy to find in the endless set of information obtainable on the World Wide Web those that essentially provide the fundamental knowledge on a particular topic.Findings: Critical thinking is a new trend in the fields of learning and comprehending methods. The author’s book embraces a complex mindset in front of the reader.Value: In this book of the series, Jonathan Haber provides a complex view to readers about the phenomena of critical thinking.
Keywords: lifelong learning; adult literacy; problem solving; analytical sills